The determinants of CEO compensation in Chinese listed family-controlled firm - Chen, Minghui (2020)
This research contributes to the corporate governance literature by examining the determinants of CEO compensation in Chinese family-controlled firms, using the data from 1,720 listed family firms and 8,403 firm-year observations from 2010 to 2018. In this research, the influences of different factors on the compensation of Chinese family CEO and non-family CEO were studied separately from the organizational level as well as the individual level. Through the investigation of the internal correlation between CEO compensation, corporate governance structure, and firm performance, this paper finds that CEO compensation is positively related to the accounting-based performance and several key corporate governance mechanisms, such as CEO duality and independence of the board. The indicators of CEO power also highly influence the design of the compensation package, for instance, the CEO compensation is increased with the percentage of CEO shareholdings. When comparing the impacts of different factors on the CEO compensation of the family CEOs and non-family CEOs, this paper finds that the compensation of external CEOs is often higher than that of family CEOs, and the family CEO compensation is more responsive to corporate performance. Most of the findings are consistent with the managerial power theory, the optimal contract theory, and the agency theory. This paper has provided some empirical evidence for further study in Chinese CEO compensation.